Electrolyte and electrochemical device including the same

By adding the compound of formula I containing pyridine ring and sulfonate groups to the electrolyte of the lithium-ion battery, the shortcomings in the storage and circulation performance of the lithium-ion battery are solved, and better cell stability and high-temperature performance are achieved.

CN119812462AActive Publication Date: 2025-04-11NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510155500.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-11
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in storage and circulation performance, especially under high temperature conditions, the stability and cycle life of the battery cell need to be further improved.

Method used

By adding a compound of formula I of a specific structure to the electrolyte, the compound contains a pyridine ring and a sulfonate group, a stable protective film can be formed at the interface between the positive and negative electrodes, and the circulation and storage performance of the battery cell are improved.

Benefits of technology

The addition of the compound of formula I significantly improves the cycling performance and high-temperature storage performance of lithium-ion batteries, ensures the stability and long life of the battery cell, and avoids the problem of increased impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812462A_ABST
    Figure CN119812462A_ABST
Patent Text Reader

Abstract

The present application provides an electrolyte and an electrochemical device comprising the same, the electrolyte comprising: a compound of formula I; in the formula, R1, R2, R3, R4 and R5 are respectively and independently selected from any one of fluorine atoms, trifluoromethyl, C1-C3 alkyl groups, cyano groups, nitryl groups, vinyl groups and ethynyl groups. Based on the technical scheme provided by the invention, the circulation and storage performance of the battery cell can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, in particular to the field of lithium-ion battery technology, and specifically to an electrolyte and an electrochemical device containing the electrolyte. Background Art

[0002] Electrochemical devices, especially lithium-ion batteries, are increasingly widely used in the field of portable electronic products. This is because electrochemical devices, especially lithium-ion batteries, have the advantages of high energy density, high operating voltage, light weight, low self-discharge rate, long cycle life, no memory effect, and environmental friendliness. In addition to smart electronic products (including mobile phones, notebooks, cameras, etc.) and energy storage products, there is an increasing demand for higher-power electronic products such as electric vehicles, power tools, drones, electric ships, etc. At the same time, the requirements for the performance of electrochemical devices are also getting higher and higher. Therefore, it is particularly important to develop electrochemical devices, especially lithium-ion batteries, with relatively low impedance and good cycle and storage performance. Summary of the invention

[0003] The purpose of this application is to provide an electrolyte and an electrochemical device containing the electrolyte to improve the storage and cycle performance of the battery cell. The specific scheme is as follows:

[0004] According to the first aspect of the present application, the present application provides an electrolyte, the electrolyte comprising: a compound of formula I;

[0005]

[0006] Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an ethynyl group.

[0007] In the technical solution provided in the present application, by adding the compound of formula I in the electrolyte, on the one hand, at the positive electrode interface, the lone pair of electrons on the nitrogen atom of the pyridine of the compound of formula I can be coordinated with the transition metal atom of the positive electrode interface, on the other hand, at the negative electrode interface, the pyridine ring of the compound of formula I can form a π-π interaction with the π electrons on the negative electrode graphite, on this basis, the lone pair of electrons on the nitrogen and the electron vacancies on the graphite form a new chemical bond, therefore, the compound of formula I can be stably adsorbed on the positive and negative electrode interface, playing a role in stabilizing the interface. In addition, the sulfonate group of the compound of formula I can also take precedence over the electrolyte in the electrochemical redox reaction at the interface, forming an interface film rich in nitrogen, sulfur, and fluorine elements, and improving the cycle and storage performance of the battery core. At the same time, the present application has found through research that the addition of nitrogen heterocyclic substances and sulfonic acid-containing or sulfur-containing substances separately will cause adverse effects on the negative electrode interface, and the impedance will be relatively large, while the use of the compound of formula I provided by the present application is appropriately added in the electrolyte, while the impedance is not deteriorated, the storage performance improvement effect is also better. In particular, the compound of formula I provided in the present application has the following structure and shows better film-forming property: (1) The nitrogen heterocyclic ring is a pyridine ring, which has a better electron distribution than the five-membered ring, and can be uniformly adsorbed at the interface, and the film-forming uniformity is better; while the electron distribution of the five-membered ring is oriented, which will lead to poor distribution uniformity of the film-forming product on the interface during film formation, affecting the improvement of circulation and storage performance. (2) The sulfonate group on the compound of formula I is connected to the C on the N heterocyclic ring (pyridine ring) through O. By connecting the pyridine ring with the sulfonate group in this way, the active site at the interface of the positive and negative electrodes can be preferentially reacted, so that the decomposition product covers the active site, inhibiting the occurrence of side reactions, and improving the circulation and storage effect. The spatial effect of the five-membered ring structure will affect the reaction at the interface, and the compound of formula I provided in the present application has a stronger adsorption effect on the interface.

[0008] In some embodiments of the present application, based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and A satisfies: 0.01%≤A≤10%; preferably, A satisfies: 0.01%≤A≤5%. When the mass content A of the compound of formula I is further controlled within the above range, the cycle and storage performance of the battery cell can be further improved. If the mass content of the compound of formula I is lower than the above range, a complete protective film cannot be formed on the interface. If the mass content of the compound of formula I is higher than the above range, the impedance of the formed interface film will increase significantly, deteriorating the cycle performance.

[0009] In some embodiments of the present application, the compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

[0010]

[0011]

[0012] In a further technical solution of the present application, the compound of formula I selects at least one of the compounds of formula I-1 to formula I-12 above, which can further improve the storage and cycle performance of the battery cell.

[0013] In some embodiments of the present application, the electrolyte further comprises a cyclic carbonate. In the present application, an appropriate amount of the cyclic carbonate is further introduced into the electrolyte as an additive, and the cyclic carbonate can be polymerized at the negative electrode interface to form a polycarbonate-rich film layer, which can effectively wrap nitrogen and sulfur elements and evenly distribute them on the negative electrode interface, promote the effect of the compound of formula I, and further improve the cycle performance of the battery cell.

[0014] In some embodiments of the present application, the electrolyte further comprises a cyclic carbonate, and based on the total mass of the electrolyte, the mass content of the cyclic carbonate is F, and F satisfies: 0.01%≤F≤10%; preferably, F satisfies: 0.1%≤F≤5%. By regulating the mass content F of the cyclic carbonate in the electrolyte within the above range, the cycle performance of the battery cell can be further improved. When the mass content of the cyclic carbonate is too low, no significant improvement effect can be achieved. When the mass content is too high, at high temperature, the cyclic carbonate is easily decomposed to produce gas, thereby deteriorating the high temperature storage performance, and the corresponding performance improvement effect cannot be achieved.

[0015] In some embodiments of the present application, the cyclic carbonate includes at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and bisfluoroethylene carbonate. In a further technical solution provided in the present application, when the cyclic carbonate is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and bisfluoroethylene carbonate, the cycle performance of the battery cell can be further improved.

[0016] In some embodiments of the present application, based on the total mass of the electrolyte, the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate satisfies the following relationship: 0.01≤A / F≤50; preferably, A / F satisfies the following relationship: 0.1≤A / F≤50. Further regulating the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate within the above range can further improve the film forming performance and further improve the battery cell cycle.

[0017] In some embodiments of the present application, the electrolyte further includes a polynitrile compound. The polynitrile compound is further added to the electrolyte, and the cyanide group of the polynitrile compound can be combined with the transition metal atom at the positive electrode interface to stabilize the positive electrode interface, while the alkyl chain thereof can be stably cross-linked at the positive electrode interface, and further promote the adsorption and film-forming reaction of the compound of formula I at the positive electrode interface, thereby reducing the side reaction of the electrolyte and further improving the storage stability of the battery cell.

[0018] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound, wherein the polynitrile compound comprises a compound of formula 1 to

[0019] At least one of the compounds represented by formula 15:

[0020]

[0021]

[0022] In a further technical solution of the present application, when the polynitrile compound is further selected from at least one of the above compounds (1)-(15), a better effect of improving the storage stability of the battery cell can be achieved.

[0023] In some embodiments of the present application, the electrolyte further includes a polynitrile compound, and based on the total mass of the electrolyte, the mass content of the polynitrile compound is N, and N satisfies: 0.05%≤N≤5%. The reduction stability of polycyano compounds at the negative electrode is poor, which will lead to instability of the negative electrode interface, thereby deteriorating the cycle performance of the battery cell. Further regulating the mass content N of the polynitrile compound in the electrolyte within the above range can reduce the reduction of excessive cyano groups at the negative electrode while improving the adsorption of the compound of formula I at the positive electrode interface, thereby achieving further improvement.

[0024] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound, and based on the total mass of the electrolyte, the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I satisfies: 0.005≤N / A≤10. Further regulating the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I within the above range can improve the adsorption of the compound of formula I at the positive electrode interface while reducing the reduction of excessive cyano groups at the negative electrode, thereby further improving the high-temperature storage and cycling effects.

[0025] In some embodiments of the present application, the electrolyte further includes a cyclic sulfur oxide compound. The cyclic sulfur oxide compound is further added to the electrolyte, and the cyclic sulfur oxide compound and the compound of formula I can participate in the solvation structure of lithium ions in the electrolyte through synergistic action, promote the uniform adsorption of the compound of formula I at the positive and negative electrodes, and the cyclic sulfur oxide compound itself can also participate in the formation of the interface film, further improving the storage performance.

[0026] In some embodiments of the present application, the electrolyte further includes a cyclic sulfur oxide compound, and the cyclic sulfur oxide compound includes at least one of 1,3-propane sultone, 2,4-butane sultone, vinyl sulfate, and vinyl sulfite. The cyclic sulfur oxide compound is selected from at least one of 1,3-propane sultone, 2,4-butane sultone, vinyl sulfate, and vinyl sulfite, which can further improve the storage performance.

[0027] In some embodiments of the present application, the electrolyte further comprises a cyclic sulfur oxide compound, and based on the total mass of the electrolyte, the mass content of the cyclic sulfur oxide compound is S, and S satisfies: 0.05%≤S≤5%. The mass content S of the cyclic sulfur oxide compound in the electrolyte is regulated within the above range, and the cyclic sulfur oxide compound can be more reasonably combined with the compound of formula I, and the two are adsorbed at the positive electrode interface through competitive reaction, which can further increase the reaction probability of the compound of formula I at the negative electrode interface, so that the positive and negative electrode surfaces are better protected, thereby further improving the storage performance.

[0028] In some embodiments of the present application, the electrolyte further includes a cyclic sulfur oxide compound, and based on the total mass of the electrolyte, the ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfur oxide compound satisfies the following relationship: 0.005≤S / A≤10. When the ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfur oxide compound is regulated within the above range, further improvement in storage can be achieved, and the impact on impedance is small.

[0029] According to the second aspect of the present application, the present application further provides an electrochemical device, the electrochemical device comprising the electrolyte described in any one of the first aspect of the present application. The electrochemical device comprising the above electrolyte has excellent high temperature storage and cycle performance. DETAILED DESCRIPTION

[0030] The technical solution of the present application is further described below through specific embodiments, which do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.

[0031] It should be noted that in the following content, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries, but can also be any other suitable secondary batteries, such as lithium metal secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries, etc.

[0032] 1. Electrolyte

[0033] According to the first aspect of the present application, the present application provides an electrolyte, the electrolyte comprising: a compound of formula I;

[0034]

[0035] Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an ethynyl group.

[0036] Specifically, the chemical formula of the "fluorine atom" is -F. The "trifluoromethyl" is a group formed by a carbon atom (C) and three fluorine atoms (F) bonded by covalent bonds, and its chemical formula is -CF3. The "C1-C3 alkyl" refers to a hydrocarbon group formed by removing a hydrogen atom from an alkane molecule with a carbon atom number between 1 and 3, usually represented by "-R", also known as an R group. The "cyano" refers to a group in which a carbon atom and a nitrogen atom are connected by a triple bond, and its chemical formula is -CN. The "nitro" refers to the group remaining after removing a hydroxyl group from a nitric acid molecule, and its chemical formula is -NO2. The "vinyl" is obtained by removing a hydrogen atom from an ethylene molecule, and its chemical formula is -HC=CH2. The "acetylene" is equivalent to a group formed by removing a hydrogen atom from an acetylene molecule, and its chemical formula is CH≡C-. Specifically, the "fluorocarboxylate" is a class of carboxylate compounds containing fluorine atoms, and its chemical formula is CnF2n+1COOR.

[0037] In the technical solution provided in the present application, by adding the compound of formula I in the electrolyte, on the one hand, at the positive electrode interface, the lone pair of electrons on the nitrogen atom of the pyridine of the compound of formula I can be coordinated with the transition metal atom of the positive electrode interface, on the other hand, at the negative electrode interface, the pyridine ring of the compound of formula I can form a π-π interaction with the π electrons on the negative electrode graphite, on this basis, the lone pair of electrons on the nitrogen and the electron vacancies on the graphite form a new chemical bond, therefore, the compound of formula I can be stably adsorbed on the positive and negative electrode interface, playing a role in stabilizing the interface. In addition, the sulfonate group of the compound of formula I can also take precedence over the electrolyte in the electrochemical redox reaction at the interface, forming an interface film rich in nitrogen, sulfur, and fluorine elements, and improving the cycle and storage performance of the battery core. At the same time, the present application has found through research that the addition of nitrogen heterocyclic substances and sulfonic acid-containing or sulfur-containing substances separately will cause adverse effects on the negative electrode interface, and the impedance will be relatively large, while the use of the compound of formula I provided by the present application is appropriately added in the electrolyte, while the impedance is not deteriorated, the storage performance improvement effect is also better. In particular, the compound of formula I provided in the present application has the following structure and shows better film-forming property: (1) The nitrogen heterocyclic ring is a pyridine ring, which has a better electron distribution than the five-membered ring, and can be uniformly adsorbed at the interface, and the film-forming uniformity is better; while the electron distribution of the five-membered ring is oriented, which will lead to poor distribution uniformity of the film-forming product on the interface during film formation, affecting the improvement of circulation and storage performance. (2) The sulfonate group on the compound of formula I is connected to the C on the N heterocyclic ring (pyridine ring) through O. The pyridine ring is connected to the sulfonate group in this way, and the reaction can be preferentially carried out at the active site of the positive and negative electrode interface, so that the decomposition product covers the active site, inhibits the occurrence of side reactions, and improves the circulation and storage effect. The spatial effect of the five-membered ring structure will affect the reaction at the interface, and the compound of formula I provided in the present application has a stronger adsorption effect on the interface. 。

[0038] In some embodiments of the present application, based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and A satisfies: 0.01%≤A≤10%. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content A of the compound of formula I can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2% %, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, or a range consisting of any two of the above values. Preferably, A satisfies: 0.01%≤A≤5%. When the mass content A of the compound of formula I is further controlled within the above range, the cycle and storage performance of the battery cell can be further improved. If the mass content of the compound of formula I is lower than the above range, a complete protective film cannot be formed on the interface. If the mass content of the compound of formula I is higher than the above range, the impedance of the formed interface film will increase significantly, thereby deteriorating the cycle performance.

[0039] In some embodiments of the present application, the compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

[0040]

[0041] In a further technical solution of the present application, the compound of formula I selects at least one of the compounds shown in the above formulas I-1 to I-12, which can further improve the storage and cycle performance of the battery cell.

[0042] In some embodiments of the present application, the electrolyte further comprises a cyclic carbonate. In the technical solutions disclosed in the prior art, carbonate is mostly used as a solvent, mainly to dissociate lithium salts or reduce the viscosity of the electrolyte, and in the present application, a cyclic carbonate is further introduced into the electrolyte as an additive, and the cyclic carbonate can be polymerized at the negative electrode interface to form a film layer rich in polycarbonate, which can effectively wrap nitrogen and sulfur elements and evenly distribute them on the negative electrode interface, promote the effect of the compound of formula I, and further improve the cycle performance of the battery cell.

[0043] In some embodiments of the present application, the electrolyte further comprises a cyclic carbonate, and based on the total mass of the electrolyte, the mass content of the cyclic carbonate is F, and F satisfies: 0.01%≤F≤10%. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content F of the cyclic carbonate can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2% %, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, or a range consisting of any two of the above values. Preferably, F% satisfies: 0.1%≤F≤5%. By regulating the mass content F of the cyclic carbonate in the electrolyte within the above range, the cycle performance of the battery cell can be further improved. When the mass content of the cyclic carbonate is too low, no obvious improvement effect can be achieved. When the mass content is too high, the cyclic carbonate is easily decomposed and gasified at high temperature, thereby deteriorating the high-temperature storage performance and failing to achieve the corresponding performance improvement effect.

[0044] In some embodiments of the present application, the cyclic carbonate includes at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and bisfluoroethylene carbonate. In a further technical solution provided in the present application, when the cyclic carbonate is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, and bisfluoroethylene carbonate, the cycle performance of the battery cell can be further improved.

[0045] In some embodiments of the present application, based on the total mass of the electrolyte, the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate satisfies the following relationship: 0.01≤A / F≤50. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3. 45, 46, 47, 48, 49, 50, or a range consisting of any two of the above values. Preferably, A / F satisfies the following relationship: 0.1≤A / F≤50. By further regulating the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate within the above range, the mass content of the compound of formula I and the cyclic carbonate added to the electrolyte can be regulated within a reasonable range, which can further improve the film forming performance and further improve the battery cell cycle.

[0046] In some embodiments of the present application, the electrolyte further includes a polynitrile compound. The polynitrile compound is further added to the electrolyte, and the cyanide group of the polynitrile compound can be combined with the transition metal atom at the positive electrode interface to stabilize the positive electrode interface, while the alkyl chain thereof can be stably cross-linked at the positive electrode interface, and further promote the adsorption and film-forming reaction of the compound of formula I at the positive electrode interface, thereby reducing the side reaction of the electrolyte and further improving the storage stability of the battery cell.

[0047] In some embodiments of the present application, the electrolyte further includes a polynitrile compound, and the polynitrile compound includes at least one of the compounds of Formula 1 to Formula 15:

[0048]

[0049] When the polynitrile compound is further selected from at least one of the compounds of Formula 1 to Formula 15, a better effect of improving the storage stability of the battery cell can be achieved.

[0050] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound, and based on the total mass of the electrolyte, the mass content of the polynitrile compound is N, and N satisfies: 0.05%≤N≤5%. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content N of the polynitrile compound can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0% or a range consisting of any two of the above values. The reduction stability of polycyano compounds at the negative electrode is poor, which will cause the negative electrode interface to be unstable, thereby deteriorating the battery cell cycle performance. When the mass content N of the polynitrile compound is further regulated within the above range, the reduction of excessive cyano groups at the negative electrode can be reduced while ensuring adsorption to the positive electrode interface to improve the compound of formula I, thereby achieving further improvement.

[0051] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound, and based on the total mass of the electrolyte, the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I satisfies: 0.005≤N / A≤10. Specifically, in some embodiments of the present application, the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7%, 0.8, 0.9, 1.0, 1.1, 1.2%, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2. 1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of the above values. Further regulating the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I within the above range can improve the adsorption of the compound of formula I at the positive electrode interface while reducing the reduction of excessive cyano groups at the negative electrode, thereby further improving the high temperature storage and cycle effect. .

[0052] In some embodiments of the present application, the electrolyte further includes a cyclic sulfur oxide compound. The cyclic sulfur oxide compound is further added to the electrolyte, and the cyclic sulfur oxide compound and the compound of formula I can participate in the solvation structure of lithium ions in the electrolyte through synergistic action, promote the uniform adsorption of the compound of formula I at the positive and negative electrodes, and the cyclic sulfur oxide compound itself can also participate in the formation of the interface film, further improving the storage performance.

[0053] In some embodiments of the present application, the electrolyte further includes a cyclic sulfur oxide compound, and the cyclic sulfur oxide compound includes at least one of 1,3-propane sultone, 2,4-butane sultone, vinyl sulfate, and vinyl sulfite. The cyclic sulfur oxide compound is selected from at least one of 1,3-propane sultone, 2,4-butane sultone, vinyl sulfate, and vinyl sulfite, which can further improve the storage performance.

[0054] In some embodiments of the present application, the electrolyte further comprises a cyclic sulfur oxide compound, and based on the total mass of the electrolyte, the mass content of the cyclic sulfur oxide compound is S, and S satisfies: 0.05%≤S≤5%. Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass content S of the cyclic sulfur oxide compound can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or more. %, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, or a range consisting of any two of the above values. The mass content S of the cyclic sulfur oxide compound is regulated within the above range, and the cyclic sulfur oxide compound can be more reasonably combined with the compound of formula I. The two are adsorbed at the positive electrode interface through competitive reaction, which can further increase the reaction probability of the compound of formula I at the negative electrode interface, so that the positive and negative electrode surfaces are better protected, thereby further improving the storage performance.

[0055] In some embodiments of the present application, the electrolyte further comprises a cyclic sulfur oxide compound, and based on the total mass of the electrolyte, the ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfur oxide compound satisfies the following relationship: 0.005≤S / A≤10. Specifically, in some embodiments of the present application, the ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfur oxide compound may be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7%, 0.8, 0.9, 1.0, 1.1, 1.2%, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1 .1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of the above values. When the ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfide compound is regulated within the above range, further improved storage can be achieved with less impact on impedance.

[0056] In some embodiments of the present application, the electrolyte provided by the present application may further include some other components, which may include but are not limited to: diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC). In some embodiments of the present application, the other components may include ether solvents, which may include but are not limited to: at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).

[0057] In some embodiments of the present application, the electrolyte provided in the present application may also include a lithium salt as an electrolyte. The lithium salt in the electrolyte includes, but is not limited to: LiClO4, LiAsF6, LiPF6, LiSbF6, LiSO3F, LiN(FSO2)2, LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium bis(oxalate)borate, lithium tris(oxalate)phosphate, lithium difluorobis(oxalate)phosphate or lithium tetrafluoro(oxalate)phosphate. In addition, the above-mentioned lithium salts can be used alone or in combination of two or more. In some embodiments, the lithium salt includes LiPF6. In some embodiments, the mass content of the lithium salt in the electrolyte is 10% to 20% based on the total mass of the electrolyte. Specifically, based on the total mass of the electrolyte, the mass content of lithium salt in the electrolyte is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of the above values.

[0058] In some embodiments of the present application, the preparation method of the electrolyte provided in the present application is not limited, and can be prepared in the manner of a conventional electrolyte. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.

[0059] 2. Electrochemical Device

[0060] According to the second aspect of the present application, the present application further provides an electrochemical device, the electrochemical device comprising the electrolyte described in any one of the first aspect of the present application. The electrochemical device comprising the above electrolyte has excellent high temperature storage and cycle performance.

[0061] In some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to: all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In some embodiments of the present application, the electrochemical device is a lithium secondary battery. In some embodiments of the present invention, the lithium secondary battery includes, but is not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery.

[0062] In some embodiments of the present application, the electrochemical device of the present application may also be a negative electrode-free battery system.

[0063] 1. Positive electrode

[0064] In some embodiments of the present application, the electrochemical device further comprises a positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The specific types of positive electrode active materials of the positive electrode active material layer are not subject to specific restrictions and can be selected according to needs. In some embodiments of the present application, the positive electrode active material comprises a lithium transition metal composite oxide. In some embodiments, the positive electrode active material is selected from at least one of the following: lithium cobalt oxide, lithium nickel manganese cobalt ternary material, lithium manganese oxide, lithium nickel manganese oxide (or lithium iron phosphate).

[0065] In some embodiments of the present application, the positive electrode active material layer further includes a binder. The binder can improve the bonding between the positive electrode active material particles and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.

[0066] In some embodiments of the present application, the positive electrode active material layer also includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0067] In some embodiments of the present application, the positive electrode current collector is a metal, such as aluminum foil.

[0068] In some embodiments of the present application, the structure of the positive electrode is a positive electrode structure that is well known in the art and can be used in a secondary battery.

[0069] In some embodiments of the present application, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery and is well known in the art. For example, the positive electrode can be obtained by the following method: a positive electrode active material, a conductive agent, and a binder are mixed in a solvent to prepare a positive electrode active material slurry, and the positive electrode active material slurry is coated on a positive electrode current collector, dried, and cold pressed to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.

[0070] 2. Negative electrode

[0071] In some embodiments of the present application, the electrochemical device further comprises a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, and the negative electrode active material is any material that can electrochemically absorb and release metal ions such as lithium ions. In some embodiments of the present application, the negative electrode active material comprises a carbonaceous material (graphite), a silicon material, a hard carbon material or a lithium metal material. In some embodiments of the present application, the negative electrode active material comprises one or more of the above.

[0072] In some embodiments of the present application, the negative electrode active material layer further includes a conductive agent to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of conductive agents include, but are not limited to: carbon-based materials, such as carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.

[0073] In some embodiments of the present application, the negative electrode active material layer further includes a thickener. The thickener may be selected from sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF).

[0074] In some embodiments of the present application, the negative electrode active material layer also includes a binder, which may include various adhesive polymers such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.

[0075] In some embodiments of the present application, the negative electrode current collector includes, but is not limited to: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.

[0076] In some embodiments of the present application, the structure of the negative electrode may be a negative electrode structure known in the art that can be used in an electrochemical device.

[0077] In some embodiments of the present application, the preparation method of the negative electrode is a preparation method of the negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing the negative electrode active material, the conductive agent, and the binder in a solvent, and heating the thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on the negative electrode current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.

[0078] 3. Isolation film

[0079] In some embodiments of the present application, the electrochemical device further comprises an isolating membrane, which is used to prevent short circuits. The material and shape of the isolating membrane are not particularly limited, and it may be any technology disclosed in the prior art. For example, in some embodiments, the isolating membrane comprises a substrate layer, which is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer may be selected from at least one of a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film. A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder, the inorganic particles can be selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate, and the binder can be selected from one or a combination of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0080] 3. Electronic equipment

[0081] The electrolyte according to the present application can enable the electrochemical device to have good high-temperature storage and cycle performance, so that the electrochemical device manufactured thereby is suitable for electronic devices in various fields.

[0082] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any use known in the prior art. In one embodiment, the electrochemical device of the present application can be used for, but not limited to: laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc. In addition, the electrochemical device provided in the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. The air vehicle includes an air vehicle in the atmosphere and an air vehicle outside the atmosphere.

[0083] Example

[0084] Hereinafter, the present application will be described in more detail by using specific examples and comparative examples.

[0085] The test methods used in the following examples and comparative examples are as follows:

[0086] (1) Lithium-ion battery DC resistance DCR test

[0087] Place the lithium-ion battery in a constant temperature environment of 0℃ and let it stand for 5 minutes to allow the lithium-ion battery to reach a constant temperature. Record the lithium-ion battery voltage at this time as U1. Discharge at a constant current of 0.1C for 10 minutes and record the lithium-ion battery voltage at this time as U2. The impedance of the lithium-ion battery at 0℃ is DCR = (U1-U2) / 0.1C.

[0088] (2) High temperature gas production performance test of lithium-ion batteries

[0089] Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge it to 4.5V at a constant current of 0.5C, and charge it to a current of 0.025C at a constant voltage of 4.5V. Record the thickness of the lithium-ion battery at this time as the initial thickness H0. Transfer the lithium-ion battery to a 60°C constant temperature box and store it for 30 days. During this period, test and record the thickness of the lithium-ion battery every 6 days. The test thickness recorded after 30 days is the storage thickness H1. High temperature storage thickness expansion rate = (H1-H0) / H0×100%.

[0090] (3) Lithium-ion battery cycle performance test

[0091] Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge to 4.5V at a constant current of 0.5C, charge to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, discharge to 3.0V at a constant current of 0.5C, record the initial discharge capacity as C0, cycle 500 times with the above charge and discharge steps, and record the discharge capacity after 100 cycles as C1. Cycle capacity retention rate = C1 / C0×100%.

[0092] Example 1-1

[0093] (1) Preparation of positive electrode

[0094] The positive electrode active material LiCoO2, the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, added into N-methylpyrrolidone (NMP) solvent, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72wt%; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the coated aluminum foil is dried at 85°C, and then after cold pressing, cutting and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode.

[0095] (2) Preparation of negative electrode

[0096] The negative electrode active material artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a weight ratio of 96:2:0.8:1.2, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry was 54wt%; the negative electrode slurry was stirred at a negative electrode active material area density of 7.8mg / cm 2 The negative electrode is evenly coated on the negative electrode current collector copper foil; the coated copper foil is dried at 85°C, and then cold pressed, cut and slit, and then dried at 120°C under vacuum conditions for 12 hours to obtain the negative electrode.

[0097] (3) Preparation of electrolyte

[0098] In a dry (water content <10ppm) argon atmosphere glove box, the solvents are mixed in a mass ratio of EC:DEC:EMC=30:40:30, and then fully dried lithium salt LiPF6 (1 mol / kg, 1M for short) is added, dissolved and fully stirred, and then the compound of formula I (Formula I-1) is added, and the electrolyte is obtained after mixing evenly; wherein, based on the total mass of the electrolyte, the mass content of the compound of formula I (Formula I-1) is 0.01%, the mass content of LiPF6 is 12.5%, and the remainder is a solvent composed of EC, DEC, and EMC.

[0099] (4) Preparation of isolation membrane

[0100] A 9 μm thick polyethylene (PE) isolation membrane was selected, and the final isolation membrane was obtained after being coated and dried with a PVDF slurry and an inorganic particle (flaky boehmite and Al2O3 in a mass ratio of 70:30). The coating thickness was 3 μm and the membrane porosity was 55%.

[0101] (5) Preparation of lithium-ion batteries

[0102] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then they are wound to obtain a bare cell; after welding the pole ears, the bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected, and then vacuum packaging, standing, formation (0.02C constant current charging to 3.3V, and then 0.1C constant current charging to 3.8V), shaping, capacity testing and other processes are carried out to obtain a soft-pack lithium-ion battery.

[0103] Example 1-2 to Example 1-22

[0104] Except for adjusting the specific type and mass content parameters of the compound of formula I according to Table 1, the remaining parameters of Examples 1-2 to 1-22 are the same as those of Example 1-1.

[0105] Comparative Example 1-1 to Comparative Example 1-4

[0106] Except for adjusting the specific type and mass content parameters of the compound of formula I according to Table 1, the other parameters of Comparative Examples 1-1 to Comparative Examples 1-4 are the same as those of Example 1-1.

[0107] According to the above test method, the impedance DCR (mΩ), high temperature storage thickness expansion rate (%), and cycle capacity retention rate (%) of the lithium ion batteries prepared by Examples 1-1 to 1-22 and Comparative Examples 1-1 to 1-4 were tested respectively, and the results are shown in Table 1:

[0108] Table 1

[0109]

[0110] According to the results presented in Table 1, adding the compound of formula I to the electrolyte can significantly improve the cycle performance of the lithium-ion battery. Moreover, by adopting the technical solution provided in the present application, the cycle performance of the lithium-ion battery is improved while the lithium-ion battery also has good impedance performance and high-temperature storage performance.

[0111] Example 2-1 to Example 2-14

[0112] Based on the results in Table 1, the corresponding embodiment further explores the effects of other components and amounts on the impedance, high temperature storage, and cycle performance of the lithium-ion battery. In addition to adjusting the specific type and mass content of the compound of formula I and the cyclic carbonate according to Table 2, the remaining parameters of Examples 2-1 to 2-14 are the same as those of Examples 1-5.

[0113] Comparative Examples 2-1 to 2-4

[0114] Based on the results in Table 1, the corresponding example further explores the effects of other components and amounts on the impedance, high temperature storage, and cycle performance of the lithium-ion battery. In addition to adjusting the specific types and mass contents of the compound of formula I and the cyclic carbonate according to Table 2, the remaining parameters of Comparative Examples 2-1 to 2-4 are the same as those of Examples 1-5.

[0115] The impedance DCR (mΩ), high temperature storage thickness expansion rate (%) and cycle capacity retention rate (%) of the lithium ion batteries prepared by Examples 2-1 to 2-14 and Comparative Examples 2-1 to 2-4 were tested according to the above test methods, and the results are shown in Table 2:

[0116] Table 2

[0117]

[0118] The results shown in Table 2 indicate that by further adding cyclic carbonate to the electrolyte, the cycle performance of the lithium-ion battery can be further improved, and the lithium-ion battery can also have good impedance performance and high-temperature storage performance.

[0119] Example 3-1 to Example 3-24

[0120] Based on the results in Table 1, the corresponding embodiment further explores the effects of other components and amounts on the impedance, high temperature storage, and cycle performance of lithium-ion batteries. Except for adjusting the specific types and mass contents of cyclic carbonates, polynitrile compounds, and cyclic sulfur oxides according to Table 3, the remaining parameters of Examples 3-1 to 3-24 are the same as those of Examples 1-5.

[0121] Comparative Examples 3-1 to 3-8

[0122] Based on the results in Table 1, the corresponding embodiment further explores the effects of other components and amounts on the impedance, high temperature storage, and cycle performance of the lithium-ion battery. In addition to adjusting the specific types and mass contents of the cyclic carbonates, polynitrile compounds, and cyclic sulfide compounds according to Table 3, the remaining parameters of Comparative Examples 3-1 to 3-8 are the same as those of Examples 1-5.

[0123] The impedance DCR (mΩ), high temperature storage thickness expansion rate (%) and cycle capacity retention rate (%) of the lithium ion batteries prepared by Examples 3-1 to 3-24 and Comparative Examples 3-1 to 3-8 were tested according to the above test methods. The results are shown in Table 3:

[0124] Table 3

[0125]

[0126]

[0127] According to the results presented in Table 3, further adding polynitrile compounds and cyclic sulfur oxide compounds to the electrolyte can further improve the cycle performance of the lithium-ion battery, and enable the lithium-ion battery to have good impedance performance and high-temperature storage performance.

[0128] It is to be understood that the present application is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the scope of the present application. In addition, under the teachings of the present application, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present application. Therefore, the present application is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present application.

Claims

1. An electrolyte, wherein The electrolyte comprises: a compound of formula I; Among them, R 1 , R 2 , R 3 , R 4 and R 5 Each is independently selected from any one of a fluorine atom, a trifluoromethyl group, a C1-C3 alkyl group, a cyano group, a nitro group, a vinyl group, and an ethynyl group.

2. The electrolyte according to claim 1, wherein Based on the total mass of the electrolyte, the mass content of the compound of formula I is A, and A satisfies: 0.01%≤A≤10%; preferably, A satisfies: 0.01%≤A≤5%.

3. The electrolyte according to claim 1, wherein The compound of formula I includes at least one of the compounds represented by formula I-1 to formula I-12:

4. The electrolyte according to claim 1, wherein The electrolyte further comprises cyclic carbonate; based on the total mass of the electrolyte, the mass content of the cyclic carbonate is F, and F satisfies: 0.01%≤F≤10%; preferably, F satisfies: 0.1%≤F≤5%.

5. The electrolyte according to claim 4, wherein The cyclic carbonate is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate and difluoroethylene carbonate.

6. The electrolyte according to any one of claims 4 to 5, wherein: Based on the total mass of the electrolyte, the ratio A / F of the mass content A of the compound of formula I to the mass content F of the cyclic carbonate satisfies the following relationship: 0.01≤A / F≤50; Preferably, A / F satisfies the following relationship: 0.1≤A / F≤50.

7. The electrolyte according to claim 1, wherein The electrolyte satisfies at least one of the following conditions (1) to (2): (1) The electrolyte further comprises a polynitrile compound; (2) The electrolyte further includes a polynitrile compound, wherein the polynitrile compound includes at least one of the compounds represented by Formula 1 to Formula 15:

8. The electrolyte according to claim 7, wherein The electrolyte satisfies at least one of the following conditions (3) to (4): (3) Based on the total mass of the electrolyte, the mass content of the polynitrile compound is N, and N satisfies: 0.05%≤N≤5%; (4) Based on the total mass of the electrolyte, the ratio N / A of the mass content N of the polynitrile compound to the mass content A of the compound of formula I satisfies: 0.005≤N / A≤10.

9. The electrolyte according to claim 1, wherein The electrolyte satisfies at least one of the following conditions (5) to (8): (5) The electrolyte further comprises a cyclic sulfur oxide compound; (6) The electrolyte further includes a cyclic sulfur oxide compound, wherein the cyclic sulfur oxide compound includes at least one of 1,3-propane sultone, 2,4-butane sultone, vinyl sulfate, and vinyl sulfite; (7) The electrolyte further comprises a cyclic sulfur oxide compound, and the mass content of the cyclic sulfur oxide compound is S based on the total mass of the electrolyte, and S satisfies: 0.05%≤S≤5%; (8) The electrolyte further comprises a cyclic sulfur oxide compound, and based on the total mass of the electrolyte, a ratio S / A of the mass content A of the compound of formula I to the mass content S of the cyclic sulfur oxide compound satisfies the following relationship: 0.005≤S / A≤10.

10. An electrochemical device, wherein: The electrochemical device comprises the electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrolyte for fluorine-containing solvent and pyridine additive and lithium ion battery using same

    CN109687022A

  • Fluorine-containing sulfonate electrolyte additive, electrolyte containing additive and lithium ion battery

    CN112054241A

  • Electrolyte, and electrochemical device and electronic device including same

    CN112271327A

  • Electrolyte for lithium ion battery and lithium ion battery

    CN116053587A

  • Electrolyte additive, electrolyte and lithium ion battery

    CN116683028A